2021
DOI: 10.1016/j.bpj.2021.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of salt-bridging interactions in recognition of viral RNA by arginine-rich peptides

Abstract: Interactions between RNA molecules and proteins are critical to many cellular processes and are implicated in various diseases. The RNA-peptide complexes are good model systems to probe the recognition mechanism of RNA by proteins. In this work, we report studies on the binding-unbinding process of a helical peptide from a viral RNA element using nonequilibrium molecular dynamics simulations. We explored the existence of various dissociation pathways with distinct free-energy profiles that reveal metastable st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…20,21,23 We produce a series of formulation buffers with different combinations of the traditional excipients, sucrose, trehalose, β-cyclodextrin, L-histidine, L-arginine, tween 20, glycerol, and polyvinylpyrrolidone (PVP). We take into consideration that L-arginine residues can contribute salt bridge interactions, 17,30 and L-histidine and PVP can form a spanning hydrogen bonded network around a protein and with other excipients. 31,32 Additionally, the hydroxyl groups in trehalose, sucrose, cyclodextrin, tween 20 and glycerol could allow for the formation of hydrogen bonds with FITC-IgG surface and OBD.…”
Section: Introductionmentioning
confidence: 99%
“…20,21,23 We produce a series of formulation buffers with different combinations of the traditional excipients, sucrose, trehalose, β-cyclodextrin, L-histidine, L-arginine, tween 20, glycerol, and polyvinylpyrrolidone (PVP). We take into consideration that L-arginine residues can contribute salt bridge interactions, 17,30 and L-histidine and PVP can form a spanning hydrogen bonded network around a protein and with other excipients. 31,32 Additionally, the hydroxyl groups in trehalose, sucrose, cyclodextrin, tween 20 and glycerol could allow for the formation of hydrogen bonds with FITC-IgG surface and OBD.…”
Section: Introductionmentioning
confidence: 99%
“…These structures of unbound and peptide-bound RRE RNA suggest that URA72 changes its conformation on binding of the P1 peptide to RRE. In a previous study of the P2 peptide unbinding from the RRE RNA, we showed that URA72 stacks on URA43 in the unbound and peptide-bound RRE RNA (Figure S10), thereby confirming these mechanistic observations. The structural analyses also revealed that the nucleotide ADE68 is oriented away from the major groove in RRE RNA in unbound states (Figure a,b), while it is oriented away toward the major groove of RRE RNA in the peptide-bound states (Figure c,d).…”
Section: Resultsmentioning
confidence: 97%
“…Many RNA binding proteins recognize RNA molecules through arginine-rich motifs (ARMs), as they are relatively shorter in length, have little sequence similarity (aside from containing many arginine residues), and adopt diverse conformations (including an α-helix and a β-hairpin) upon association with the viral RNA. The experimental work using X-ray crystallography and nuclear magnetic resonance (NMR) methods on the peptide–RNA complexes has demonstrated that the RNA backbone interacts with peptides more commonly than the nucleotide bases, suggesting that the majority of peptide–RNA interactions are nonspecific. , Overall, these studies showed that the peptide–RNA interactions occur through dynamic rearrangements in both molecules, which often entail backbone shifts and the flipping of nucleobases and amino acid residues. , Moreover, recent studies have demonstrated that the β-hairpin peptides could be synthesized with ultrahigh affinity toward viral RNA molecules. However, a de novo design of α-helical peptides that potently and selectively recognize viral RNA molecules is limited due to a poor understanding of the RNA recognition mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found through earlier structural, classical simulation, and quantum chemical studies that ATP generally binds at the active site of aaRS in a bent conformation with its α-phosphate pointed toward the adenine base and its β- and γ-phosphate moieties oriented toward the opening of the active site. ,,,, For all class II aminoacyl tRNA synthetases, the adenine ring of ATP gets stacked with the conserved phenylalanine of motif 2 and arginine of motif 3 . Also, the invariant motif 2 arginine binds rather strongly with the α-phosphate of ATP, while one Mg 2+ ion bridges the α- and β-phosphates. ,, The presence of one or two additional Mg 2+ ions bridging the β- and γ-phosphates of ATP has also been reported in earlier experimental and theoretical studies. ,,,,, Recent simulations have shown that the conserved motif II arginine residue makes contact with both the α-phosphate and attacking oxygen of the carboxylic group of the substrate amino acid and thus helps in anchoring the substrates ATP and amino acid in the reactive conformation. ,, This residue has also been reported to stabilize the transition states of both the activation and transfer steps. ,, Experimental and quantum chemical studies on the effects of mutation of the motif 2 arginine have also shown its important role in catalytic reactions at the active site of class II aminoacyl tRNA synthetases. ,,, The important role of arginine residues has also been reported for biomolecular recognitions involving other proteins and RNA. , …”
Section: Introductionmentioning
confidence: 99%